Service provider barriers to treatment and care for people with mental health and alcohol and other drug comorbidity in a metropolitan region of South Australia. Issue 3 (17th August 2015) - de Crespigny, Charlotte; Grønkjær, Mette; Liu, Dennis; Moss, John; Cairney, Imelda; Procter, Nicholas; Posselt, Miriam; Francis Jebaraj, Hepsibah Sharmil; Schultz, Tim; Banders, Andris; King, Rosie; Lee, Deb; et al.
Abstract : Purpose: – The purpose of this paper is to elicit clinicians' and workers' knowledge, experiences and opinions of key issues pertaining to comorbidity service needs of people aged 12 years and over in a metropolitan region of South Australia. Design/methodology/approach: – As one component of a participatory action research project, this qualitative study used semi-structured interviews with mental health (MH) and alcohol and other drug (AOD) clinicians and workers ( n =20). Findings: – The participants expressed concerns involving stigma towards their clients. They highlighted lack of adequate MH and AOD comorbidity service accessibility and models, regularly available clinical comorbidity workforce development, and practice supervision and skills training. These factors influenced participants' and their colleagues' capacity and ability to access and provide appropriate help for people needing integrated treatment and care of their co-existing comorbid conditions. Practical implications: – Findings highlight the need for coordinated and integrated, individualised holistic comorbidity services, including treatment and care best suited to Aboriginal people and refugees. Originality/value: – This study emphasises the importance of government and non-government MH and AOD services ensuring that comorbidity is responded to collaboratively and systemically. It also demonstrates the importance of professional development.